2017
DOI: 10.1002/lary.26890
|View full text |Cite
|
Sign up to set email alerts
|

Positive fresh frozen section margins as an adverse independent prognostic factor for local recurrence in oral cancer patients

Abstract: 4. Laryngoscope, 128:1093-1098, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 29 publications
1
30
1
Order By: Relevance
“…Three studies showed that patients with positive (<1 mm) margins cleared (≥1 mm) under FS guidance had poorer local control compared to those with initially clear (≥1 mm) margins. 11,13,14 Buchakjian et al 11 also showed that patients with positive margins cleared had comparable LR rates to those with persistently positive margins. Two studies showed that patients with positive (0 mm) margins cleared to negative (≥5 mm) had worse LRFS compared to those with initially negative (≥5 mm) margins.…”
Section: Resultsmentioning
confidence: 96%
“…Three studies showed that patients with positive (<1 mm) margins cleared (≥1 mm) under FS guidance had poorer local control compared to those with initially clear (≥1 mm) margins. 11,13,14 Buchakjian et al 11 also showed that patients with positive margins cleared had comparable LR rates to those with persistently positive margins. Two studies showed that patients with positive (0 mm) margins cleared to negative (≥5 mm) had worse LRFS compared to those with initially negative (≥5 mm) margins.…”
Section: Resultsmentioning
confidence: 96%
“…Multiple investigations have tried to assess the impact of tumor cut‐through on long‐term control outcomes . Ettl et al found that, in a study of patients with head and neck SCC of various sites and subsites, initially positive FS margins translated to an overall recurrence rate of 42% compared to 16.2% in those with initially negative margins .…”
Section: Resultsmentioning
confidence: 99%
“…Patients with a positive FS margin also had lower disease‐free survival irrespective of stage of disease. Thus, the authors advocated that tumors requiring re‐resection to achieve negative margin status should be considered for adjuvant therapy . Conversely, in a retrospective cohort of 547 patients with OSCC, Patel et al suggested that in patients without regional disease, those requiring re‐resection to achieve negative margins behave similarly to those with initially negative margins.…”
Section: Resultsmentioning
confidence: 99%
“…8,[11][12][13] Despite the widespread use of FS, recent studies have shown that initially positive margins lead to worse outcomes than initially negative margins regardless of whether re-resection guided by FS was performed. 4,[14][15][16][17] Additionally, some studies have demonstrated that patients undergoing simple gross examination of the resection specimen have similar clear margin rates and outcomes compared to those having FS. 18,19 Ninety percent of surgeons reported that revision of a positive margin under FS guidance results in a negative margin, despite a lack of evidence for this claim.…”
Section: Introductionmentioning
confidence: 99%